The Influence of the Environment on Understanding the Arabic Language Lesson for Eighth Grade Students at Secondary School | تأثير البيئة لفهم الدرس اللغة العربية لطلبة الفصل الثامن في المدرسة الثانوية - Wahab, Abdul; Syaifullah, Muhammad; Roza, Ahmad Subhan (NAJAH BESTARI, 2024)
The environment has a big influence on students' understanding of Arabic language lessons. This research aims to determine the influence of the environment, especially the family, school and community environment, on the understanding of Arabic language lessons for class VIII students at MTs Darun Najah Sambikarto. This research uses a quantitative approach with a quasi-experimental method. Data collection techniques are carried out through observation, interviews, tests and documentation. Data were analyzed using validity, reliability, normality, homogeneity and hypothesis testing. From the posttest results, a significant value was obtained of 0.007 <0.05. Where the significant value obtained is <0.05, the hypothesis that reads is